Impact of SARS-CoV-2 Alpha variant (B.1.1.7) on prisons, England. (March 2022) - Vusirikala, Amoolya; Flannagan, Joe; Czachorowski, Maciej; Zaidi, Asad; Twohig, Kate A.; Plugge, Emma; Ellaby, Nicholas; Rice, Wendy; Dabrera, Gavin; Chudasama, Dimple Y.; Lamagni, Theresa
Abstract: Objectives: Prisons are high-risk settings for infectious disease outbreaks because of their highly dynamic and crowded nature. During late 2020, prisons in England observed a surge in COVID-19 infection. This study describes the emergence of the Alpha variant in prisons during this period. Methods: Alpha and non-Alpha variant COVID-19 cases were identified in prisoners in England using address-matched laboratory notifications and genomic information from COG-UK. Results: Of 14, 094 COVID-19-positive prisoner cases between 1 October 2020 and 28 March 2021, 11.5% (n = 1621) had sequencing results. Of these, 1082 (66.7%) were identified as the Alpha variant. Twenty-nine (2.7%) Alpha cases required hospitalisation compared with only five (1.0%; P  = 0.02) non-Alpha cases. A total of 14 outbreaks were identified with the median attack rate higher for Alpha (17.9%, interquartile range [IQR] 3.2%–32.2%; P  = 0.11) than non-Alpha outbreaks (3.5%, IQR 2.0%–10.2%). Conclusion: Higher attack rates and increased likelihood of hospitalisations were observed for Alpha cases compared with non-Alpha. This suggests a key contribution to the rise in cases, hospitalisations and outbreaks in prisons in the second wave. With prisons prone to COVID-19 outbreaks and the potential to act as reservoirs for variants of concern, sequencing of prison-associated cases alongside whole-institution vaccination should be prioritised.